Effects of Scale on Multimodal Deixis: Evidence From Quiahije Chatino - Mesh, Kate; Cruz, Emiliana; van de Weijer, Joost; Burenhult, Niclas; Gullberg, Marianne (Frontiers in Psychology, 2021)
Humans interact in the world, and often orient one another’s attention to objects within it. To do this we typically produce a spoken expression--often a demonstrative like this or that--alongside movements of the head and/or hand to point to the object. Pointing and demonstratives function jointly: they contribute distinct but complementary information to help narrow down the space in which to search for an object. Studies have explored these linked behaviors in laboratory settings, investigating how people direct attention to objects around them. Yet we know surprisingly little about how demonstratives and pointing are used to coordinate attention in large-scale space, or about how they are used in natural contexts. Here we present a first study of how speakers use demonstratives and pointing to pick out objects in large-scale space. We study this activity in speakers of Quiahije Chatino, an indigenous language of Mexico where prior research has already provided information about the language's demonstrative system, and about community pointing practices. We analyze how speakers use demonstratives and pointing as they give directions to named places at multiple scales. Our study reveals that strategies for using pointing and demonstratives change as the scale of search space for the target grows. Importantly, they suggest that pointing is the more informative indicating behavior, and plays a central role in the multimodal indicating act, when the target is in large-scale space.